2014
DOI: 10.1016/j.tate.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Teacher beliefs about listening in a foreign language

Abstract: Teacher beliefs about listening in a foreign language. Teaching and Teacher Education, 40. pp. 44-60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 35 publications
4
67
0
16
Order By: Relevance
“…In spite of areas such as literacy (McNeill & Kirk, 2013), grammar (Uysal & Bardakci, 2014), and content areas (Goldhaber & Brewer, 2000) which have witnessed research on the correspondence between teachers' beliefs and practices abundantly, an area which has received little attention in the literature has been teachers' beliefs about listening and their beliefs-driven practices (Graham, Santos, & Francis-Brophy, 2014). Listening as the most difficult skill for learners (Martinez-Flor & Usó-Juan, 2006) requires teachers' full adherence to cultivating the basic mechanisms of how listening works in the learners.…”
Section: Former [Espoused Theory] Is Comprised Of Explicit Beliefs Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of areas such as literacy (McNeill & Kirk, 2013), grammar (Uysal & Bardakci, 2014), and content areas (Goldhaber & Brewer, 2000) which have witnessed research on the correspondence between teachers' beliefs and practices abundantly, an area which has received little attention in the literature has been teachers' beliefs about listening and their beliefs-driven practices (Graham, Santos, & Francis-Brophy, 2014). Listening as the most difficult skill for learners (Martinez-Flor & Usó-Juan, 2006) requires teachers' full adherence to cultivating the basic mechanisms of how listening works in the learners.…”
Section: Former [Espoused Theory] Is Comprised Of Explicit Beliefs Thmentioning
confidence: 99%
“…Considering this point, it is of high significance to explore teachers' listening theories and their listening instructional behaviors. Regarding teachers' beliefs about listening comprehension, Graham et al (2014) conducted a study to explore the listening beliefs of 115 Modern Foreign Language (MFL) teachers in England, how they used listening materials in textbooks, and the nature of those materials. The results indicated a mismatch between teachers' stated beliefs regarding listening instruction and their stated practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Listening is probably the most difficult skill to learn since it seems to be the least explicit of the four language skills (Graham, Santos, & Francis-Brophy, 2014). According to Richards and Schmidt (2007), listening comprehension can be defined as the process of understanding speech in a first or second language which needs a conscious plan to deal with incoming speech problems due to incomplete understanding of the listener.…”
Section: Listening Comprehension Skillmentioning
confidence: 99%
“…However, recent studies of L2 listening instruction have revealed that many teachers rarely incorporate BU processing in their listening lessons (e.g., Graham, Santos, & Francis-Brophy, 2014;Siegel, 2014). An expansion in pedagogic practices to include more BU techniques is needed as this area is typically overlooked and because many of the listening difficulties L2 learners experience have been attributed to BU obstacles.…”
Section: Pedagogic Suggestionsmentioning
confidence: 99%
“…Moreover, based on findings from questionnaires, class observations, and teacher interviews, language educators are often lacking in practical approaches, techniques and activities that they can apply in their classrooms (Graham, Santos, & Francis-Brophy, 2014;Graham, Santos, & Vanderplank, 2011). Further, teachers who turn to textbook teacher manuals for help may find little support for listening (Field, 2012).…”
Section: Introductionmentioning
confidence: 99%